Наукові основи технології кольорових екологічно безпечних склоемалей - Рижова, Ольга Петрівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.17.11 – технологія тугоплавких неметалічних матеріалів, Державний вищий навчальний заклад "Український державний хіміко-технологічний університет", Національний технічний університет "Харківський політехнічний інститут". Дисертацію присвячено науковим основам технології екологічно безпечних склоемалевих покриттів широкої колірної гами для сталі і кольорових металів, розробці принципів регулювання та прогнозування їх кольору. Розроблена спеціальна комп’ютерна програма COLOUR GLASS, яка за визначеними координатами кольору XYZ автоматично розташовує точки кольору на графіку МКО. Отримані емалі ювелірного та художнього призначення на основі стекол системи Na₂O–BaO–B₂O₃–SiO₂. Розроблені малофлуористі білі і світлозабарвлені титанові емалі, безфлуориста основа для пігментного способу забарвлення. Створено метод колірного моделювання, за допомогою якого можна розрахувати співвідношення пігментів для відтворення кольору зразка за заданими колірними характеристиками.

Thesis for a Doctor of Science Degree in Specialty 05.17.11 Refractory Non-Metallic Materials Technology, State Higher Educational Institution "Ukrainian State University of Chemical Technology", National Technical University "Kharkiv Polytechnic Institute". The dissertation is devoted to development of scientific bases of technology of ecologically safe protective and decorative glass-enamel coatings of wide color scale on steel and non-ferrous metals, making of principles of regulation and prediction of their color. The introduction substantiates the relevance of the dissertation topic, formulates the main purpose and objectives of the work. The first section provides an analysis of the patent and scientific and technical literature. The second section provides the basic concepts and definitions used in the work, methods for investigating the physicochemical properties and structure of glasses and coatings and their color characteristics. The third section presents studies on the development of environmentally safe enamels for copper and the prediction of their color characteristics. The fourth section presents the results of studies on the development of small fluoride titanium enamel with a firing temperature of 830 °C. The fifth section had devoted to scientific bases of technology of fluorless enamel frits for pigment method of coloring. The sixth section has devoted to the development of the color modeling method for reproducing the color of a sample with specified color characteristics. In the seventh section the results of industrial testing, implementation and implementation of the received materials has presented. As a result of the research on the topic of dissertation the following scientific results has obtained: - scientifically substantiated and experimentally proved that the production of lead-free enamel coatings on non-ferrous metals is possible on the basis of the Na₂O–BaO–B₂O₃–SiO₂ glasses, the regions of glass formation has been determined, and the regularities of changes in the properties of glasses depending on their chemical composition has been established; - the main tendencies of change of glasses color tone has established in the Na₂O–BaO–B₂O₃–SiO₂ system, which has colored by ionic dyes given the structural features of the glasses and their acid-base properties; - it has been proved that the degree of color intensity of glasses in the system R₂O –BaO – ZnO – Al₂O₃ – B₂O₃ – TiO₂ – SiO₂ and coatings based on them has been arranged in the following sequence: CoO> NiO> CuO> K₂Cr₂O₇> Fe₂O₃; - for the first time the mechanism of opacifying of transparent matrix enamel glass in the R₂O – BaO – ZnO – TiO₂ – Al₂O₃ – B₂O₃ – TiO₂ – SiO₂ system was introduced when MoO₃ has been established, namely: due to diffraction, which results in the phenomenon of opalescence; - for the first time the dependence of the diffuse reflection coefficient of enamel coatings on the chemical composition of enamel frits has been established, which is presented in the form of a mathematical model; the correlation coefficient between experimental and calculated values is 0.98; - for the first time the mechanism of opacifying of transparent matrix enamel glass in the R₂O – BaO – ZnO – TiO₂ – Al₂O₃ – B₂O₃ – TiO₂ – SiO₂ system was introduced when MoO3 has been established, namely: due to diffraction, which results in the phenomenon of opalescence; - for the first time it has been discovered that Fe₂O₃ "small additive" in the amount of 0.25 wt.% in the composition of lead-free enamel glasses on the basis of the Na₂O – BaO – B₂O₃ – SiO₂ base system and 1 wt. Fe₂O₃ in the composition of fluor-free enamel glasses on the basis of the Na₂O – B₂O₃ – SiO₂ base system activates the processes of glass removal stratification, which allows to increase 1.5-2.5 times the intensity of coating damping; - with the help of a special computer program COLOR GLASS, which automatically calculates the coordinates of the color x, y, the color tone λ, the purity of the color P and applies the color characteristics of the materials to the CIE graph, it has been proved for the first time that the chart of the location of color points can make forecasts about the equilibrium, which formed between ionic coloring complexes during glass melting; - for the first time in the field of technologies requiring high temperatures, the dependences of the color coordinates of enamel coatings on the composition of the pigment mixture in the form of polynomial mathematical models has been established, which allowed to solve the complex material-coloristic problem of finding the ratio of pigments to reproduce the color of the sample with the specified color characteristics. The practical significance of the obtained results: - the compositions of enamel art and jewelry glasses for non-ferrous metals, which do not contain Plumbum, has been developed. They are characterized by the same firing interval of 780-820 °C. A catalog of color samples has created. The palette includes fondon and 53 colors: yellow-red, blue-green, olive-mustard, pastel and brown-black; - a series of compositions of white and light-colored titanium enamels containing reduced amount of Fluorine (up to 2.5 wt.%), has been developed, also the composition of fluorless frites to obtain brightly colored enamel coatings pigmented way of color. Temperature operations of the enamel melting is 100 °C and firing of coatings is 30-50oC below the known ones.
Scientific foundations of colored environmentally safe glass enamel technology
Keywords: автореферат дисертації; склоемаль; Флуор; Плюмбум; іонне забарвлення скла; пігмент; титанове покриття; прогнозування кольору; колірний тон; чистота кольору; палітра; художні вироби; ювелірні вироби; glass enamel; Fluorine; Plumbum; ionic glass coloring; pigment; titanium coating; color prediction; color tone; color purity; palette; art wares; jewelry wares; 666.293.522